2021
DOI: 10.3390/ijms22052616
|View full text |Cite
|
Sign up to set email alerts
|

Robust Detection of Somatic Mosaicism and Repeat Interruptions by Long-Read Targeted Sequencing in Myotonic Dystrophy Type 1

Abstract: Myotonic dystrophy type 1 (DM1) is the most complex and variable trinucleotide repeat disorder caused by an unstable CTG repeat expansion, reaching up to 4000 CTG in the most severe cases. The genetic and clinical variability of DM1 depend on the sex and age of the transmitting parent, but also on the CTG repeat number, presence of repeat interruptions and/or on the degree of somatic instability. Currently, it is difficult to simultaneously and accurately determine these contributing factors in DM1 patients du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 50 publications
1
42
0
1
Order By: Relevance
“…The occurrence of different types and patterns of variant repeats indicates that they probably originate by rare base substitutions within the pure (CTG)n array then spread along the expansion during processes involved in DNA metabolism. Rare findings of de novo occurring CTC [ 40 ] and CCG [ 43 , 44 ] variant repeats support this hypothesis of their origin.…”
Section: Variant Repeats In the (Ctg)n Array Of The Dmpk Genementioning
confidence: 82%
See 3 more Smart Citations
“…The occurrence of different types and patterns of variant repeats indicates that they probably originate by rare base substitutions within the pure (CTG)n array then spread along the expansion during processes involved in DNA metabolism. Rare findings of de novo occurring CTC [ 40 ] and CCG [ 43 , 44 ] variant repeats support this hypothesis of their origin.…”
Section: Variant Repeats In the (Ctg)n Array Of The Dmpk Genementioning
confidence: 82%
“…Although Aci I digestion was more commonly used for patient screening [ 36 , 43 , 46 ], it is of note that studies relying on RP-PCR also identified CCG repeat as the most common interruption [ 37 , 40 ]. Proof-of-concept studies have demonstrated the potential of PCR-based long-read PacBio sequencing technology to overcome the aforementioned limitations [ 43 , 44 ]. Harnessing long-read sequencing technologies will certainly bring a more complete picture of structural variations of not only DMPK expansions, but other expansions as well, including DM2.…”
Section: Variant Repeats In the (Ctg)n Array Of The Dmpk Genementioning
confidence: 99%
See 2 more Smart Citations
“…Des fibroblastes contenant plusieurs centaines de répétitions CTG seront traités par ces molécules candidates ou du DMSO sur une période de trois mois, temps nécessaire pour observer et quantifier la mosaïque somatique (temps estimé sur la base de nos expériences précédentes). La mosaïque somatique des répétitions CTG dans les différentes cultures cellulaires sera mesurée en utilisant la dernière technologie de séquençage à longue lecture développée par Pacific Biosciences (Figure 3) [13,14] Cette technologie de séquençage permet de mesurer la taille des répétitions molécule par molécule et ainsi d'étudier la distribution de la mosaïque somatique dans les cellules traitées et leurs contrôles respectifs. Parallèlement, la prolifération cellulaire et la cytotoxicité pour différentes doses de drogues seront testées en utilisant un système d'imagerie automatisée qui permet de suivre l'évolution des cellules en temps réel (Incucyte ® , Sartorius).…”
Section: Conclusion Et Perspectives Du Projetunclassified